2010
DOI: 10.4330/wjc.v2.i8.243
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation and inflammation

Abstract: Atrial fibrillation (AF) is the most common clinical arrhythmia. Recent investigations have suggested that inflammation might have a role in the pathophysiology of AF. In this review, the association between inflammation and AF, and the effects of several agents that have anti-inflammatory actions, such as statins, polyunsaturated fatty acids, corticosteroids and angiotensin-converting enzyme inhibitors and angiotensin receptor blockers, have been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 88 publications
1
24
0
Order By: Relevance
“…responsible for the development of atrial fibrillation [1,3,17]. Even the atrial pathoanatomy in lone atrial fibrillation showed inflammatory infiltration, muscle cell necrosis and fibrosis [1,17]. Modern research has confirmed that chronic inflammation has arrhythmogenic effect giving rise to the development of AF in susceptible populations.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…responsible for the development of atrial fibrillation [1,3,17]. Even the atrial pathoanatomy in lone atrial fibrillation showed inflammatory infiltration, muscle cell necrosis and fibrosis [1,17]. Modern research has confirmed that chronic inflammation has arrhythmogenic effect giving rise to the development of AF in susceptible populations.…”
Section: Discussionmentioning
confidence: 97%
“…Inflammation is closely associated to atrial fibrillation [6] and may be the important medium which links atrial fibrillation with known risk factors (such as high blood pressure and obesity, etc.) responsible for the development of atrial fibrillation [1,3,17]. Even the atrial pathoanatomy in lone atrial fibrillation showed inflammatory infiltration, muscle cell necrosis and fibrosis [1,17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Atrial fibrillation (AF) is the most common cardiac arrhythmia and increases in prevalence with aging [1][2][3]. It has become one of the leading causes for hospitalized patients with AF because AF may induce stroke, heart failure and increases case fatality [1,2,4].…”
Section: Introductionmentioning
confidence: 99%